Penerapan Arsitektur Perilaku Pada Perancangan Panti Wreda di Kabupaten Majene - Lutfi, Lutfi; Zulkarnain AS; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2024)
Abstract_ The increasing number of elderly people in Indonesia each year presents a significant challenge for both the government and society. One of the issues arising from this demographic shift is the growing population of neglected elderly individuals, categorized as part of the social welfare problem (PMKS), who require special attention to ensure they have a decent quality of life. Therefore, designing a safe and comfortable residential facility for neglected elderly individuals is crucial. This study aims to design a housing facility that meets these needs, providing a dignified living space while supporting the well-being of the elderly. The research employs an architectural design approach, analyzing the spatial requirements suitable for neglected elderly people while considering safety and comfort factors. The results indicate that the proposed design can provide spaces that meet the physical and psychological needs of the elderly, while also emphasizing accessibility and security. According to data from the Social Services Office of Majene Regency, the number of neglected elderly individuals was recorded at 172 in 2019, 128 in 2020, and increased to 279 in 2021, highlighting the urgent need for residential facilities for neglected elderly people.